Hubungan Dukungan Keluarga terhadap Tingkat Kekambuhan Pasien Skizofrenia di Poliklinik Rumah Sakit Jiwa Aceh - Khaira Rizki; Nurul Amna; Dian Fadillah; Ellyza Fazlylawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Schizophrenia is a serious mental illness that requires long-term treatment and carries a high risk of recurrence. The recovery process for patients relies not only on medical intervention, but also requires optimal involvement and support from their families. The presence of a supportive family is believed to strengthen patient motivation and contribute positively to their psychological well-being. This study aims to identify the relationship between family support and relapse rates in schizophrenia patients undergoing treatment at the Aceh Mental Hospital Polyclinic. This study uses a correlational design with a Cross-Sectional method. Through Accidental Sampling, 114 samples were selected from a population of 3,233 individuals. Data collection took place between April 14 and 28, 2025, using a questionnaire focused on family support and relapse rates. To analyze the relationship between the two variables, a Chi-Square statistical test was applied. The main findings of the study show that aspects of family support in general (p=0.000), informational support (p=0.000), appreciative support (p=0.000), instrumental support (p=0.001), and emotional support (p=0.002) are correlated with the recurrence rate of patients. Based on the analysis of the results, it can be concluded that there is a correlation between family support and the recurrence of schizophrenia patients at the Aceh Mental Hospital Polyclinic. The practical implications of this research are expected to serve as a reference for the families of schizophrenia patients to increase their understanding and activity in providing support, including consulting with mental health professionals as an effort to prevent possible recurrence.